2017
DOI: 10.1101/237420
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A single-cell catalogue of regulatory states in the ageing Drosophila brain

Abstract: SummaryThe diversity of cell types and regulatory states in the brain, and how these change during ageing, remains largely unknown. Here, we present a single-cell transcriptome catalogue of the entire adult Drosophila melanogaster brain sampled across its lifespan. Both neurons and glia age through a process of "regulatory erosion", characterized by a strong decline of RNA content, and accompanied by increasing transcriptional and chromatin noise. We identify more than 50 cell types by specific transcription f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…Furthermore, reports published so far on mapping of coexpression to specific neurons are likely to cover only a small fraction of the actual cases. This is suggestive from a few recent reports analyzing transcriptomes of single dissociated cells in the Drosophila brain where preliminary data already uncovered plenty of new combinations of colocalized substances ( Abruzzi et al, 2017 ; Croset et al, 2017 ; Davie et al, 2017 ) shown in Tables 3 , 4 . These novel data constitute a rich source for future systematic mapping of neuropeptides and SMNs to neurons and circuits in the brain of Drosophila by imaging techniques.…”
Section: Concluding Remarks and Future Perspectivessupporting
confidence: 70%
See 2 more Smart Citations
“…Furthermore, reports published so far on mapping of coexpression to specific neurons are likely to cover only a small fraction of the actual cases. This is suggestive from a few recent reports analyzing transcriptomes of single dissociated cells in the Drosophila brain where preliminary data already uncovered plenty of new combinations of colocalized substances ( Abruzzi et al, 2017 ; Croset et al, 2017 ; Davie et al, 2017 ) shown in Tables 3 , 4 . These novel data constitute a rich source for future systematic mapping of neuropeptides and SMNs to neurons and circuits in the brain of Drosophila by imaging techniques.…”
Section: Concluding Remarks and Future Perspectivessupporting
confidence: 70%
“…The studies discussed above are based on traditional imaging techniques and have probably only revealed the tip of the iceberg. Recently, reports on single-cell transcriptomics of dissociated Drosophila brain neurons discovered numerous additional patterns of colocalized neuropeptides and neuropeptides with SMNs ( Abruzzi et al, 2017 ; Croset et al, 2017 ; Davie et al, 2017 ), shown in Tables 3 , 4 . Although this type of analysis substantially increased the cases of likely colocalization of neuropeptides and monoamines, as well as other SMNs, it provides little information on which specific types of neurons that express the substances.…”
Section: Neuroactive Compounds That Have Been Found Colocalized In Nementioning
confidence: 99%
See 1 more Smart Citation
“…Our initial analysis was performed on 10,286 of the highest quality cells (≥800 UMIs) from a larger dataset of 19,260 cells. This atlas is effectively a scaffold that can now be continuously updated and expanded as additional cells are collected and sequenced ( Davie et al, 2017 ; Konstantinides et al, 2018 ). Our current dataset was derived from cells taken from unique groups of flies, processed on eight separate days, and yet each biological replicate contributed equally to the combined data set.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, co-expression of the dopamine synthesizing enzyme Tyrosine Hydroxylase (TH) in a few neurons marked by an FMRFaGAL4 (48), suggests the existence of an autocrine signaling mechanism within the flight modulating dopaminergic neurons. This idea is supported by recent studies of single cell sequencing of Drosophila neurons where FMRFa transcripts were seen in a small number of central brain dopaminergic neurons (49, 50). Interestingly, a recent report from Manduca demonstrated that an FMRFa positive neuron lies at the center of a putative sensory-motor circuit for integration of olfactory stimuli with wing movements during flight (51).…”
Section: Discussionmentioning
confidence: 71%